Land-use changes and practical application of the land degradation neutrality (LDN) indicators: a case study in the subalpine forest ecosystems, Republic of Korea - Cha, Sangsub; Kim, Chan-Beom; Kim, Jeonghwan; Lee, Ah Lim; Park, Ki-Hyung; Koo, Namin; Kim, Yong Suk (Forest science and technology, 2020)
Recent estimates show that land degradation is rapidly progressing worldwide. Therefore, efforts are being made in Korea toward Land Degradation Neutrality (LDN) to extend the development of green areas. As part of this effort, artificial ecosystems created through land-use changes are restored to forests. We examined grassland created through land-use change, an afforested site planted for forest restoration, and a nearby primary forest according to the LDN indicators. The grassland created about 40 years ago showed higher bulk density and available phosphorus compared to the forest and showed relatively low carbon and nitrogen contents. According to the assessment of LDN indicators, the soil organic carbon stock and productivity calculated from the normalized difference vegetation index of the afforested site for restoring the grassland to forest did not change. The assessment of the restoration effect was not made in the short-term, but in near future, the planted trees are expected to grow, restoring the land to forest. This study shows that the LDN program of Korea should follow carefully established restoration policies and strategies to achieve positive results.